PENGHILANGAN PAKSA SEBAGAI KEJAHATAN TERHADAP KEMANUSIAAN (TELAAH PUTUSAN PRA-PERADILAN III ICC ATAS SITUASI BURUNDI) - Ashri, Abdul Munif; Giovanny, Hans (Arena Hukum, 2023)
Enforced disappearance could be qualified as a crime against humanity. However, international human rights law (IHRL) and international criminal law (ICL), have different definitions of enforced disappearance. It can be reviewed by the different formulations between the ‘ICPPED’ and the Rome Statute of the ‘ICC’. Rome Statute adds several elements to the enforced disappearance definition, such as ‘specific intent’ by the individual perpetrators, ‘temporal element’, and ‘political organization’ as potential actors. And the Pre-Trial Chamber (PTC) III Decision on ‘Burundi Situation’ (2017) could be a significant reference. By the doctrinal research through statute and conceptual approach, this article concludes that the PTC III Decision reflects the very close relationship between those two different branches of law, as PTC III still refers to IHRL instruments to fill the legal gap in the interpretation of enforced disappearance within the Rome Statute.